Diana Holmes. Middlebrow Matters: Women’s reading and the literary canon in France since the Belle Époque. Liverpool UP, 2018. - Dantzel Cenatiempo (Studies in 20th & 21st Century Literature, 2020)
Review of Diana Holmes. Middlebrow Matters: Women’s reading and the literary canon in France since the Belle Époque. Liverpool UP, 2018. 222 pp.
Keywords: middlebrow; Belle Époque; France; women& #x27; s writing; Diana Holmes; Colette; Françoise Sagan; Marie N’Diaye